Tumor-Draining Lymph Secretome En Route to the Regional Lymph Node in Breast Cancer Metastasis - Mohammed SI (Dove Medical Press, 2020)
Sulma I Mohammed,1,2 Odalys Torres-Luquis,1 Weidong Zhou,3 Nadia Attalah Lanman,1,2 Virginia Espina,3 Lance Liotta3 1Department of Comparative Pathobiology, Purdue University, West Lafayette, IN 47907, USA; 2Purdue University Center for Cancer Research, Purdue University, West Lafayette, IN 47907, USA; 3Center for Applied Proteomics and Molecular Medicine, George Mason University, Manassas, VA 20110, USACorrespondence: Sulma I MohammedDepartment of Comparative Pathobiology, Purdue University, 610 Purdue Mall, West Lafayette, IN 47907 USATel +1765-494-9948Fax +1765-494-9830Email mohammes@purdue.eduBackground: During metastasis, tumor cells metastasize from primary tumors to distant organs via the circulatory and the lymphatic systems. There is a plethora of information about metastasis through the circulatory system, however not much information is available about the tumor cells dissemination through the lymphatic system or the lymphatic microenvironment that aids in this process in breast cancer metastasis.Purpose: The study designed to examine the tumor-derived secretome in lymph before reaching the draining lymph nodes.Methods: Using a microsurgical technique, we have collected the lymph in transit from the primary tumor en route to the regional lymph node in animals with metastatic and non-metastatic mammary carcinoma and healthy controls. The lymph samples were subjected to LC-MS/MS analysis, bioinformatics, and pathway analysis.Results: The metastatic tumor-draining lymph before its entry into the closest regional lymph node contain 26 proteins with > 175-folds in abundance compared to lymph from non-metastatic tumor-bearing animals. Among these proteins were biliverdin reductase B, heat shock protein, coagulation factor XIII, lymphocytes cytosol protein 1, and aldose reductase. These proteins were not identified in the lymph from healthy animals. Pathways analysis revealed that cadherin-mediated endocytosis, acute phase response, junction signaling, gap junction, VEGF singling, and PI3K/AKT singling pathways are overrepresented in the lymph from metastatic tumor-bearing compared to the lymph from non-metastatic tumor-bearing animals. Among the significantly up-regulated proteins in the lymph from metastatic tumor-bearing animals were proteins that identified in exosomes include heat shock protein, enolase 1 alpha, S100, and biliverdin reductase B. One of the proteins significantly down-regulated in lymph from animals with metastasis is Kininogen, a known metastasis inhibitor protein.Conclusion: Proteins and exosomal proteins in lymph draining a metastatic tumor are different from those in lymph draining non-metastatic tumors, and these proteins involved in pathways that regulate tumor cells migration and invasion.Keywords: lymph, lymphatic vessels, cancer, breast, lymph node, metastasis, exosome, tumor-derived factors